Hemostasis during the early stages of trauma: comparison with disseminated intravascular coagulation - Oshiro, Akiko (BioMed Central, 2014)
INTRODUCTION: We tested two hypotheses that disseminated intravascular coagulation (DIC) and acute coagulopathy of trauma-shock (ACOTS) in the early phase of trauma are similar disease entities and that the DIC score on admission can be used to predict the prognosis of patients with coagulopathy of trauma. METHODS: We conducted a retrospective study of 562 trauma patients, including 338 patients whose data were obtained immediately after admission to the emergency department. We collected serial data for the platelet counts, global markers of coagulation and fibrinolysis, and antithrombin levels. DIC was diagnosed according to the Japanese Association for Acute Medicine (JAAM) DIC scoring system, and ACOTS was defined as a prothrombin-time ratio of >1.2. RESULTS: The higher levels of fibrin/fibrinogen degradation products (FDP) and D-dimer and greater FDP/D-dimer ratios in the DIC patients suggested DIC with the fibrinolytic phenotype. The DIC patients with the fibrinolytic phenotype exhibited persistently lower platelet counts and fibrinogen levels, increased prothrombin time ratios, higher FDP and D-dimer levels, and lower antithrombin levels compared with the non-DIC patients on arrival to the emergency department and during the early stage of trauma. Almost all ACOTS patients met the criteria for a diagnosis of DIC; therefore, the same changes were observed in the platelet counts, global markers of coagulation and fibrinolysis, and antithrombin levels as noted in the DIC patients. The JAAM DIC score obtained immediately after arrival to the emergency department was an independent predictor of massive transfusion and death due to trauma and correlated with the amount of blood transfused. CONCLUSIONS: Patients who develop DIC with the fibrinolytic phenotype during the early stage of trauma exhibit consumption coagulopathy associated with increased fibrin(ogen)olysis and lower levels of antithrombin. The same is true in patients with ACOTS. The JAAM DIC score can be used to predict the prognosis of patients with coagulopathy of trauma.